Selective conversion of nitrate to nitrogen by CuNi alloys embedded mesoporous carbon with breakpoint chlorination. (August 2021) - Yao, Xinyun; Yu, Bei; Xue, Yinghao; Ran, Xianqiang; Zuo, Jiaqi; Qiu, Kaipei
Abstract: The electrocatalytic reduction of nitrate, a common contaminant in surface and ground water, to the harmless nitrogen gas is a promising technology that can be potentially energy efficient and environmentally friendly. The bottleneck hindering its large-scale implementation is mainly attributed to the unsatisfactory selectivity toward the final product N2 . To solve this challenge, a two-step strategy was applied here, in which the NO3 − was first reduced to NH4 + at the cathode, followed with a rapid non-electrochemical oxidation to N2 by the ClO − generated from anodic breakpoint chlorination. Note that the formation of ClO − may be easily controlled and enhanced by the dosage of Cl − ions, the overall nitrate removal efficiency for the above process was determined by its NO3 − to NH4 + activity. The high-performance copper-nickel alloys embedded mesoporous carbon electrocatalysts were therefore rationally designed, which exhibited a complete conversion of NO3 − in the absence of Cl −, and furthermore, a 100% N2 selectivity with the addition of Cl − . Using density functional theory calculations, it was verified that the incorporation of Ni atoms into Cu interface significantly enhanced the adsorption of *NHOH and *NH2 OH intermediates, lowering the barrier of *NOH hydrogenation to *NH3 (NH4 + ). Besides, the nitrogen-containing ordered mesoporous carbon support not only facilitated the synthesis of uniformly distributed CuNi nanoparticles (ca. 20 nm), but also ensured the sufficient mass and charge transfer, as well as the high durability. Graphical abstract: Unlabelled Image Highlights: The 100% NO3 − to N2 was done through a selective reduction to NH4 +, then oxidation. Well-dispersed CuNi nanoelectrocatalysts facilitated the NO3 − conversion to NH4 + . Ordered mesoporous carbon support guaranteed the efficient mass/charge transfer. A 90% NO3 − removal efficiency was realized over 60 h of continuous operation.